2005
DOI: 10.1016/j.visres.2004.10.024
|View full text |Cite
|
Sign up to set email alerts
|

Attentional effects on contrast discrimination in humans: evidence for both contrast gain and response gain

Abstract: In order to understand how attention affects visual processing, we investigated the degree to which attention effects can be accounted for by increases in the contrast gain of the contrast response function, CRF (represented by an increase in effective contrast) vs. increases in the response gain (represented by an overall amplification of response). To this end, we used a dual-task paradigm to compare psychophysical "threshold vs. pedestal contrast" (TvC) curves obtained under conditions of full- vs. poor-att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
134
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(151 citation statements)
references
References 23 publications
16
134
1
Order By: Relevance
“…For example, a study by Huang and Dobkins (2005) showed reduced contrast sensitivity when participants were asked to engage in contrast discrimination under dual task conditions. These attentional effects were most pronounced close to the contrast threshold for successful detection of the visual stimuli, and the authors found the effects to primarily affect early areas in the visual system.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a study by Huang and Dobkins (2005) showed reduced contrast sensitivity when participants were asked to engage in contrast discrimination under dual task conditions. These attentional effects were most pronounced close to the contrast threshold for successful detection of the visual stimuli, and the authors found the effects to primarily affect early areas in the visual system.…”
Section: Discussionmentioning
confidence: 99%
“…We manipulated the allocation of voluntary attention using a single/dual task paradigm. This paradigm has been extensively used to investigate the involvement of attention in various visual processes as diverse as motion processing (Thiele et al 2002;Thornton et al 2002), stimulus localization (Adam et al 2008), contrast discrimination (Huang and Dobkins 2005;Alais et al 2006) and contextual modulation (Zenger et al 2000). Attention is a broad term covering a wide range of cognitive processes (Knudsen 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Attending to low luminance contrast stimuli increases their apparent contrast (Carrasco et al 2004), and boosts neuronal responses to match responses elicited by higher contrast stimuli (Reynolds et al 2000;Martinez-Trujillo and Treue 2002;Williford and Maunsell 2006). Thus attending to a stimulus has been suggested to be equivalent to increasing its luminance contrast (Carrasco et al 2004;Huang and Dobkins 2005). The similarity between increasing contrast and attending to a stimulus has resulted in the "contrast gain model" of attention (Reynolds et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…In psychophysical studies, covert shifts of attention (also termed 'transient' attention) tend to decrease the increment stimulus threshold (the smallest contrast increment that can be reliably detected) for all baseline contrasts (Carrasco, Ling & Read, 2004;Huang & Dobkins, 2005;Ling & Carrasco, 2007), though it has also been suggested that this enhanced contrast sensitivity may be due to sensory interactions instead (Schneider, 2006). Likewise, studies using single-cell recordings have demonstrated that contrastdependent neuronal responses can also be enhanced by attention (Reynolds, Pasternak & Desimone, 2000;Martinez-Trujillo & Treue, 2002), regardless of whether attention is shifted exogenously or endogenously .…”
Section: Attentionmentioning
confidence: 99%